Postpartum Uterine Bacterial Contamination without Clinical signs in Rela-tion to Reproductive Performance in Dairy Cows - Tawfek M. Barakat; G. Shawky; Mohamed A.M. Ragab (مجلة المختار للعلوم, 2019)
The study was performed to find out the relation between the uterine bacterial contaminations without clinical signs and postpartum (PP) reproductive performance of dairy cows. So that, uterine bacterial samples from postpartum dairy cows total (n = 44) were taken at 3rd, 15th and 30th day, and the bacterial count and score were applied. The animals were grouped to low, medium and high uterine bacterial contamination (15, 15, and 14 cows for each group respectively) according to score. Results revealed that uterine bacterial score (UBS) was decreased by the time in 3rd, 15th and 30th day (PP) for Low bacterial contamination group (5.73, 2.80, and 1.20 respectively), for Medium bacterial contamination group (7.80, 2.73,  and 1.47 respectively), and for High bacterial contamination group (9.29, 6.57, and 2.21 respectively). Also, it revealed that there was a significant increase (P<0.05) in the duration of lochia in High than Low and Medium bacterial contamination groups. At 3rd day (PP), uterine location in all cows was represented in the abdominal cavity, but at15th day (PP), uterine involution as reaching to its normal non pregnant position in pelvic cavity was delayed in High (50%) than Low (80 %,) and Medium (53.30%) UBS groups. Moreover, at 30th day, uterine location in all cows was represented in pelvic cavity. The first estrus (PP) was significantly shorter in Medium, Low than High UBS groups. The number of services per conception showed a significant increase in High than in Low and Medium UBS groups. Also, at the 90th day (PP), the conception rate was lower in High UBS group than Low UBS group and Medium UBS group. We conclude that there was a relation between postpartum uterine bacterial contamination without clinical signs especially high contamination and reproductive performance in cows.